2012
DOI: 10.1371/journal.pone.0038063
|View full text |Cite
|
Sign up to set email alerts
|

A DNA Barcode Library for North American Ephemeroptera: Progress and Prospects

Abstract: DNA barcoding of aquatic macroinvertebrates holds much promise as a tool for taxonomic research and for providing the reliable identifications needed for water quality assessment programs. A prerequisite for identification using barcodes is a reliable reference library. We gathered 4165 sequences from the barcode region of the mitochondrial cytochrome c oxidase subunit I gene representing 264 nominal and 90 provisional species of mayflies (Insecta: Ephemeroptera) from Canada, Mexico, and the United States. No … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 35 publications
5
93
1
Order By: Relevance
“…However, a fixed threshold of COI sequences is not appropriate for all taxonomic groups. In insects for instance, a 2% threshold provides effective identification at the species level of Ephemeroptera (Schmidt et al 2015;Webb et al 2012;Zhou et al 2010), Lepidoptera (Zahiri et al 2014) and Trichoptera (Zhou et al 2016), while a 2.2% threshold appears appropriate for Heteroptera (Knebelsberger et al 2014), 2.5% for aquatic beetles (Monaghan et al 2005), and >3% for various dipteran groups (Nzelu et al 2015;Renaud et al 2012). Furthermore, an average threshold of 4-5% appears appropriate for most Chironomidae (Lin et al 2015;Meier et al 2015), even if a 7% threshold has been reported for closely related species in this family (Carew & Hoffmann 2015).…”
Section: Dna Barcodes and Morphospeciesmentioning
confidence: 99%
“…However, a fixed threshold of COI sequences is not appropriate for all taxonomic groups. In insects for instance, a 2% threshold provides effective identification at the species level of Ephemeroptera (Schmidt et al 2015;Webb et al 2012;Zhou et al 2010), Lepidoptera (Zahiri et al 2014) and Trichoptera (Zhou et al 2016), while a 2.2% threshold appears appropriate for Heteroptera (Knebelsberger et al 2014), 2.5% for aquatic beetles (Monaghan et al 2005), and >3% for various dipteran groups (Nzelu et al 2015;Renaud et al 2012). Furthermore, an average threshold of 4-5% appears appropriate for most Chironomidae (Lin et al 2015;Meier et al 2015), even if a 7% threshold has been reported for closely related species in this family (Carew & Hoffmann 2015).…”
Section: Dna Barcodes and Morphospeciesmentioning
confidence: 99%
“…Thus, it cannot be automatically assumed that COI lineages, which are that far apart, represent different species, without testing this with nuclear data. This again illustrates how problematic it is to delimit species with a DNA-barcoding gap as the sole criterion, in Clitellata (e.g., Achurra and Erséus 2013;Martinsson et al 2013Martinsson et al , 2015Martinsson and Erséus 2017) as well as in other animal groups (e.g., Munoz et al 2011;Webb et al 2012;Hogner et al 2012) …”
Section: Discussion Species Delimitationmentioning
confidence: 95%
“…The use of molecular marker sequences to assist in determining species has been a positive step toward addressing the problems of identifying species from life stages and material for which there are no useful traditional taxonomic keys. Webb et al (2012) used the COI marker sequence to confirm the co-occurrence of P. midas and P. chelifer in samples from Churchill, Manitoba. Their consensus analysis of sequence divergence values also showed a strong association of samples of P. midas from Manitoba and New Brunswick with clear separation from samples of P. chelifer.…”
Section: Introductionmentioning
confidence: 99%